(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Ultrasound elastography (USE) is an ultrasound-based technique that addresses the biomedicalproperties of the nodules. Based on the stiffness of the tissue this technique differentiates between the benignnodules from the malignant ones where the hard and soft tissue is determined by the high or the low elasticityvalues respectively. The present study aimed to evaluate the efficacy of the E-thyroid in the differentiationof malignant and benign thyroid nodules and also a cut off ECI value using fine-needle aspiration as thediagnostic standard of referenceMethods: The current prospective study was done on 80 patients in the radiology department in Al Yarmoukteaching hospital in Baghdad city from April 2018 to April 2019. All the patients referred from the outpatientclinic. All the patients were examined sonographically starting with B mode ultrasound then elastoscanexamination was done.Result: The study result showed that among the 80 patients 65 had a benign nodule and only 15 werediagnosed with a malignant thyroid nodule. The ECI value and the histopathological result showed asignificant agreement in the result and a cut off ECI value of 4 were shown to be effective to diagnose thepresence of malignant thyroid nodule.Conclusion: Overall, the present study showed that USE can be effectively used to differentiate between themalignant and benign thyroid nodules and being a safe method this can be used widely. However, the resultof this study needs further validation with a larger study population.